ChemInform Abstract: Aminocarbonylation of (Hetero)aryl Bromides with Ammonia and Amines Using a Palladium/DalPhos Catalyst System. Issue 15 (25th March 2013) - Alsabeh, Pamela G.; Stradiotto, Mark; Neumann, Helfried; Beller, Matthias
Abstract Ammonia acts as both nucleophile and base in these reactions.